Cultural Pragmatics in the Classroom: The Role of Local Markers in Indonesian EFL Discourse - Dinihari, Yulian; Boeriswati, Endry; Prima, Anggra; Noviabahari, Jannatul Laily; Cromico, Jimmy (Indonesian Scientific Publication, 2025)
This study investigates the interactional functions of local pragmatic markers (PMs) in Indonesian English as a Foreign Language (EFL) classrooms. While pragmatic markers such as okay and so are widely documented in global academic discourse, local markers like kan, dong, and sih remain underexplored. The objective of this research is to analyze how these culturally embedded markers support pedagogical interaction and contribute to classroom discourse management. Data were taken from transcripts of six Indonesian EFL classes. A corpus-based approach was applied using the IRF (Initiation–Response–Feedback) model and function-based coding. Marker frequency was normalized per 1,000 words and categorized by speaker role, turn position, and discourse function. To provide comparison, data from the MICASE and ELFA corpora were also analyzed. Results show that local PMs serve both textual and interpersonal functions. Teachers used kan to affirm responses, dong to encourage participation, and nah to mark procedural shifts. These markers enhanced Classroom Interactional Competence by facilitating smoother transitions, reducing student anxiety, and promoting learner engagement. Compared to MICASE and ELFA, which lack these markers, the Indonesian classrooms demonstrated a discourse style shaped by cultural values such as consensus and relational harmony. The findings highlight the pedagogical significance of integrating local pragmatic norms into EFL instruction. Recognizing and leveraging these markers can enhance communicative effectiveness and cultural inclusivity in language education. This study contributes to expanding models of pragmatic competence and affirms the importance of localized discourse analysis in multilingual educational contexts.